2022
DOI: 10.1007/s00011-021-01526-2
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of benzylisoquinoline alkaloids by resting and activated bone marrow-derived mast cells utilizes energy-dependent mechanisms

Abstract: Objective and design Drug delivery to inflammatory cells is dependent upon poorly understood, complex endocytic processes. Berberine (BBR), a benzylisoquinoline alkaloid, binds to heparin and targets glycosaminoglycan-rich granules in mast cells (MC), but the mechanism of BBR internalization is unknown. Methods BMMC were treated with various concentrations of BBR for different amounts of time and BBR internalization was assessed by flow cytometry and fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Mast cells are a tissue-resident innate immune cell that mediate tissue homeostasis but also facilitates inflammatory disease 21 . Unlike lymphocytes, mast cells are large, granular and extremely difficult to transfect using conventional non-viral strategies 22 , 23 . We hypothesized that Apos may facilitate the internalization of cationic LNPs into terminally differentiated mouse bone marrow-derived mast cells (BMMC).…”
Section: Introductionmentioning
confidence: 99%
“…Mast cells are a tissue-resident innate immune cell that mediate tissue homeostasis but also facilitates inflammatory disease 21 . Unlike lymphocytes, mast cells are large, granular and extremely difficult to transfect using conventional non-viral strategies 22 , 23 . We hypothesized that Apos may facilitate the internalization of cationic LNPs into terminally differentiated mouse bone marrow-derived mast cells (BMMC).…”
Section: Introductionmentioning
confidence: 99%
“…2C). We have demonstrated that BBR internalizes into resting and IL-3-activated BMMC by utilizing energy-dependent active transport mechanism that is dependent upon glucose metabolism and temperature [40]. Moreover, internalization of BBR into metabolically active BMMC is time-dependent.…”
Section: Internalization Of Berberine Into Cellsmentioning
confidence: 92%
“…Mast cells are a tissue-resident innate immune cell that mediate tissue homeostasis but also facilitates in ammatory disease [21]. Unlike lymphocytes, mast cells are large, granular and extremely di cult to transfect using conventional non-viral strategies [22,23]. We hypothesized that Apos may facilitate the internalization of cationic LNPs into terminally differentiated mouse bone marrow-derived mast cells (BMMC).…”
Section: Introductionmentioning
confidence: 99%